RETURN SAHAM: CORPORATE SOCIAL RESPONSIBILITY DAN MODERASI GOOD CORPORATE GOVERNANCE - Aryani, Kharisma Dwi; Mutmainah, Ina; Apriliantika, Annisa (Perwira Journal of Economics & Business, 2025)
The average stock return in 2021 the average stock return will increase rapidly by 67% because the government, OJK, and Bank Indonesia are working together to carry out various stimulus methods so that the economy can return to stability. In addition, the existence of innovations in terms of banking digitization and CSR implementation has made investors start to look back at banking stocks. From this incident the company seemed to realize that CSR can effectively affect stocks with Good Corporate Governance Mechanisms as a Moderating Variable in Banking Sector Companies Listed on the IDX for the 2021-2023 Period. This research uses a quantitative method that uses secondary data in the form of annual reports and sustainability reports that the company publishes. The sample in this study was selected using a purposive sampling method so that the sample used was 55 companies in the banking sector. The simple regression analysis method and the Moderated Regression Analysis (MRA) test were used in this study to test the hypothesis proposed by the researcher. The results of this study indicate that the CSR variable has a significant effect on stock returns, institutional ownership is not able to strengthen the moderating effect of CSR on stock returns, managerial ownership is able to strengthen the effect of CSR on stock returns, independent commissioners are not able to strengthen CSR moderation on stock returns, and the audit committee is not able to strengthen the influence of CSR on stock returns.